Juridical Implications of Village Financial Management Based on Law Number 6 Of 2014 Concerning Villages in Realizing Good Village Governance (Good Governance) - Sari, Noca Yolanda (YHMM PUBLISHING, 2023)
Village is entity smallest from A where is the Indonesian government, recognized and respected based on constitution. Existence village in a manner juridical poured in regulation Law No. 6 of 2014 concerning Village. Objective from development village is with increase well-being from public village as well as increase quality life as well as effort in matter countermeasures number poverty through method fulfillment need base community, development from potency economy local, development facilities and infrastructure village as well as utilization source Power nature and environment in a manner sustainable. Draft finance village with draft state finances, that is through mechanism Budget Income and Spending Village that consists from part income, spending and financing village, which is carried out by the Head The village and its tools are discussed together with the Consultative Body Village. Management finance village implicated juridical for Head Village and Consultative Body Village For can compile, legitimize, implement, supervise and account for management finance village to use realizing good village governance (good governance). If anything negligence or on purpose, then will resulted accountability Good in a manner administrative nor criminal. Government Regency/City is obliged allocate budget for finance village, as well do coaching and supervision.